2016
DOI: 10.25268/bimc.invemar.2002.31.0.292
|View full text |Cite
|
Sign up to set email alerts
|

Crecimiento De Juveniles De Pargo Palmero Lutjanus Analis (Cuvier) en Jaulas Flotantes en Islas Del Rosario, Caribe Colombiano

Abstract: An experimental culture trial of juveniles of mutton snapper Lutjanus analis was conducted in order to evaluate the growth potential of the species and its adaptability to culture conditions. The juveniles (N = 127) with an initial weight ranging between 125 and 178 g were held at a stocking density of 15.9 fish/m3 in a floating cage and fed on a commercial artificial diet of 45% protein for a period of 1 to 8 days. Results showed an individual daily weight increase of 3.16 g/ day and a specific growth rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…The Absolute Growth Rate (AGR) found in D2 (Table 2) places L. pacificus among a select group of species with high growth rates, such as Rachycentron canadum with 16.7 and 12.1 g day -1 (Benetti et al 2010); Epinephelus itajara with 6.83 and 12.4 g day -1 (Botero & Ospina, 2003); Seriola rivoleana with 5.3 g day -1 (Benitez- Hernández et al 2017), Oreochromis niloticus with values recorded between 3.29 and 4.47 g day -1 (Lima-Amancio et al 2014), Lutjanus analis with 3.16 g day -1 (Botero & Ospina, 2002), Sciaenops ocellatus with 2.7 g day -1 (Vela et al 2018), and Lutjanus guttatus with 1.58 g day -1 (Castillo-Vargasmachuca et al 2016). Compared to juveniles of other commercial marine fish studied in recirculation systems, SGR of L. pacificus was lower than the range reported by Webb et al (2007) for R. canadum (5.18 to 5.29% BW day -1 ) and by Do-Huu et al (2018) for Trachinotus ovatus (3.15 to 3.26% BW day -1 ), but similar to the one reported by Palstra et al (2015) for Seriola lalandi (2.1%BW/day -1 ), and superior to the values reported by authors such as Weirich et al (2009) for Trachinotus carolinus (0.81% BW day -1 ), Álvarez-González et al (2001) for Paralabrax maculatofasciatus (1.73% BW day -1 ), and Merino et al (2007) for Paralichthys californicus (1.18% BW day -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Absolute Growth Rate (AGR) found in D2 (Table 2) places L. pacificus among a select group of species with high growth rates, such as Rachycentron canadum with 16.7 and 12.1 g day -1 (Benetti et al 2010); Epinephelus itajara with 6.83 and 12.4 g day -1 (Botero & Ospina, 2003); Seriola rivoleana with 5.3 g day -1 (Benitez- Hernández et al 2017), Oreochromis niloticus with values recorded between 3.29 and 4.47 g day -1 (Lima-Amancio et al 2014), Lutjanus analis with 3.16 g day -1 (Botero & Ospina, 2002), Sciaenops ocellatus with 2.7 g day -1 (Vela et al 2018), and Lutjanus guttatus with 1.58 g day -1 (Castillo-Vargasmachuca et al 2016). Compared to juveniles of other commercial marine fish studied in recirculation systems, SGR of L. pacificus was lower than the range reported by Webb et al (2007) for R. canadum (5.18 to 5.29% BW day -1 ) and by Do-Huu et al (2018) for Trachinotus ovatus (3.15 to 3.26% BW day -1 ), but similar to the one reported by Palstra et al (2015) for Seriola lalandi (2.1%BW/day -1 ), and superior to the values reported by authors such as Weirich et al (2009) for Trachinotus carolinus (0.81% BW day -1 ), Álvarez-González et al (2001) for Paralabrax maculatofasciatus (1.73% BW day -1 ), and Merino et al (2007) for Paralichthys californicus (1.18% BW day -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The survival rates of spotted rose snapper in this study were similar to those observed for yellowtail snapper, Ocyurus chrysurus (García et al ), raised in floating net cages at a lower density. However, for the mutton snapper, Lutjanus analis , slightly higher (97.6%) (Botero and Ospina ) and lower (70%) (Benetti et al ) survival rates have been reported. The overall survival rate of 70% can be considered satisfactory (Benetti et al ).…”
Section: Discussionmentioning
confidence: 96%
“…Já as ações de prospecção de espécies aptas para produção em cativeiro no estado do Ceará têm verificado que, dentre as espécies de peixes marinhos apontados como propícias à produção em cativeiro, estão dois Lutjanídeos: Lutjanus synagris e Lutjanus analis (Watanabe et al, 1998;Benetti et al, 2002;Ospina, 2002;Vettorazzi et al, 2010;Cerqueira et al, 2017). Porventura, a produção comercial de Lutjanídeos já é uma realidade em vários países, como Costa Rica (L. guttatus), Hon Kong (L. russelli), Taiwan (L. bohar), Singapura (L. goldiei), Filipinas (L.…”
Section: Desafios E Perspectiva Da Piscicultura Marinha No Estado Do unclassified